The enforcement of law regarding the school bus / Mohamad Izwan Mohamed Noh, Mazuin Hashim and Muhammad Hafidz Hassan. - Mohamed Noh, Mohamad Izwan; Hashim, Mazuin; Hassan, Muhammad Hafidz (2007)
This research is carried up for the purpose of studying and understanding the current situations involving the school bus law in Malaysia. The school bus services are highly accepted by the Malaysian society as the most convenient transportation for the school children in reaching their respective school. Nevertheless, school buses can be involved in tragic accidents which may cause injury or death to its passengers. This research will examine all the relevant provisions in the current local statutes which govern the school bus services in finding out whether these laws are sufficient to ensure the safety of the innocent passengers. Furthermore, the references to foreign laws are also made. Relevant articles from the United States of America and Canada have been analyzed and extracted. Most of the articles are based on American law since they have their very own laws to govern their school bus services. From these articles, recommendations are made to be the flesh that covers the loopholes of local school bus law. The recommendations are post based on the two main ideas namely the safety of the school children in using the school bus services and also the positive duty principles of other road users towards the school bus. As a conclusion, this research is expected to raise the public awareness about the matters involving the school bus services. Several weaknesses in the local law have been identified and the recommendations are made but it is up to the authority to take the necessary steps.